SPOTIGHT on Duvha - Doris Gardner (The Southern African Institute of Mining and Metallurgy, 1986)
On Friday, 6th June, 1986, an SAIMM party of32 set out at 06h30 for a tour of Duvha Opencast Colliery, Lesedi Village, and Duvha Power Station-all situated just outside Witbank. Duvha Colliery On arrival at the mine, the party was met by Mr. Colin Kolver, Assistant General Manager, and the guides for the morning. After refreshments had been served, Mr. MacDonald, General Manager, welcomed the tour, and a series of slides on the opencast mine and Lesedi Village were shown.